Shakespeare and the folktale : an anthology of stories - Artese, Charlotte, 1973- (Princeton University Press, 2019)
"An international collection of the traditional tales that inspired some of Shakespeare's greatest plays. Shakespeare knew a good story when he heard one, and he wasn't afraid to borrow from what he heard or read, especially traditional folktales. The Merchant of Venice, for example, draws from "A Pound of Flesh," while King Lear begins in the same way as "Love Like Salt," with a king asking his three daughters how much they love him, then banishing the youngest when her cryptic reply displeases him. This unique anthology presents more than forty versions of folktales related to eight Shakespeare plays: The Taming of the Shrew, The Comedy of Errors, Titus Andronicus, The Merchant of Venice, All's Well That Ends Well, King Lear, Cymbeline, and The Tempest. These fascinating and diverse tales come from Europe, the Middle East, India, the Caribbean, and South America, and include stories by Gerald of Wales, Marie-Catherine d'Aulnoy, Jacob and Wilhelm Grimm, Giambattista Basile, J. M. Synge, Zora Neale Hurston, Italo Calvino, and many more. Organized by play, each chapter includes a brief introduction discussing the intriguing connections between the play and the gathered folktales. Shakespeare and the Folktale can be read for the pure pleasure these lively tales give as much as for the insight into Shakespeare's plays they provide."--provided by publisher.